Case Report: Uncommon co-occurrence of different renal histopathological entities in a patient with multiple myeloma and lymphoplasmacytic lymphoma - Talarico, Marco; Vischini, Gisella; Barbato, Simona; Restuccia, Roberta; Masci, Simone; Sacchetti, Ilaria; Manzato, Enrica; Ghibellini, Stefano; Puppi, Michele; Iezza, Miriam; Rizzello, Ilaria; Pantani, Lucia; et al. (Frontiers in Oncology, 2025)
In patients with plasma cell dyscrasias presenting with kidney injury, renal biopsy usually displays the presence of a single histological damage. However, the coexistence of heterogeneous damages has been occasionally described and is associated with worse renal outcomes. In this report, we describe the case of a patient with a concomitant diagnosis of multiple myeloma and lymphoplasmacytic lymphoma, presenting with acute kidney injury and with renal biopsy revealing the unexpected concurrent presence of several different renal damages, who achieved a good hematologic response and dialysis independence after anti-myeloma therapy.